Apatinib treatment may improve survival outcomes of patients with hepatitis B virus-related sorafenib-resistant hepatocellular carcinoma. (July 2020) - Zhang, Yingqiang; Huang, Guihua; Miao, Hongfei; Song, Ze; Zhang, Xiaoying; Fan, Wenzhe; Wang, Yu; Li, Jiaping; Chen, Yong
Aims: This study aimed to (a) assess the effectiveness and safety of apatinib as a subsequent treatment for patients with sorafenib-resistant hepatocellular carcinoma (HCC), and (b) identify the clinical factors influencing their treatment outcomes. Methods: The electronic medical records of consecutive patients with newly diagnosed advanced HCC treated with first-line sorafenib from 2015 to 2017 were retrospectively reviewed. Patients who were confirmed to have primary resistance to sorafenib were enrolled in this study. The outcomes of patients treated with apatinib were compared with those of patients who received supportive care. The primary endpoint was overall survival (OS). Results: A total of 92 patients with sorafenib-resistant advanced HCC (84 men and 8 women; mean age, 51.9 years) were included. All patients had an etiology of hepatitis B. The median OS in the overall cohort was 5.0 months [95% confidence interval (CI): 3.9, 6.0]. Of 92 patients, 58 (63.0%) were treated with apatinib, and 34 (37.0%) received supportive care. Apatinib treatment was associated with longer survival times than supportive care for patients with sorafenib-resistant advanced HCC (median OS: 7.0 versus 4.0 months, p < 0.001). The results of the multivariate analysis demonstrated that liver tumor load [hazard ratio (HR): 3.653, 95% CI: 2.047, 5.965, p < 0.001] and extrahepatic spread (HR: 0.303, 95% CI: 0.231, 0.778, p = 0.003) were independent predictors of OS after apatinib treatment. Conclusion: This study showed that subsequent apatinib treatment may improve survival outcomes compared with supportive care for patients with sorafenib-resistant, advanced hepatitis B virus (HBV)-related HCC, especially for patients who have a lower liver tumor load and extrahepatic spread.